A study of compliance to DOTS among tuberculosis patients attending a district hospital, Uttar Pradesh - Upadhyay, Shalini; Upadhyay, Nishant (International Journal Of Community Medicine And Public Health, 2019)
Background: Tuberculosis is an old disease and has deep social impact on the society. It is a re-emergent killer disease with rise in MDR and XDR strains. DOTS strategy under RNTCP has had a substantial impact over the past two decades. Treatment compliance is one of the key factors determining success of TB control program. The objective of this study was to find out the compliance rate with DOTS and factors responsible for non-compliance in the district. Methods: A cross-sectional study was carried out using structured questionnaire in a tuberculosis unit of Chandauli district, Uttar Pradesh. 100 tuberculosis patients aged ≥15 years registered for TB treatment were enrolled in the study. Results: Out of the 100 patients interviewed, majority of patients (95%) complied. The main reasons for non-compliance were improvement in symptoms after initial doses leading to discontinuation of therapy, and side effects of drugs. One of the defaulter migrated, so he could not be traced. Among factors influencing compliance to DOTS most important was strong monitoring. Conclusions: Health education and easy accessibility of healthcare services are required to further improve the compliance of TB treatment. Internet tools and social security schemes can play essential role in increasing awareness and strengthening the monitoring program.